Accelerating Second Language Acquisition for Effective Strategies for Student - Tiya Anisyah Firdaus; Ahmad Munir; Syafi'ul Anam (Publikasi Indonesia, 2024)
This study examines the importance of expediting the acquisition of a second language (SLA), with a particular emphasis on techniques and approaches that improve the effectiveness of language learning. Based on ten participants—English teachers and students—in structured interviews, the study investigates the advantages, phases, and practical approaches for second language acquisition. It has been demonstrated that expediting SLA enhances communication abilities, scholastic achievement, and cognitive growth, providing useful benefits in professions like tourism. In order to improve the acquisition process, the study emphasizes the value of immersion, cognitive and metacognitive techniques, and using the first language. By being aware of these components, teachers can better adapt their instruction and help students become proficient more quickly. The results imply that in order to maximize language learning outcomes, a comprehensive strategy that takes into account individual learner characteristics and stages of acquisition is necessary and empowering students to actively participate in the global society.